Pola Kerjasama Pemanfaatan Data dan Inovasi Pelayanan Publik pada Dinas Kependudukan Pencatatan Sipil Kota Serang - Dian Imanuella (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The use of population data plays a crucial role in improving the quality of public services and supporting data-driven policymaking. The Population and Civil Registration Service (Disdukcapil), as the agency responsible for population administration, is responsible for providing accurate, up-to-date, and integrated population data. This study aims to analyze collaborative patterns of population data utilization and public service innovation at the Serang City Population and Civil Registration Service. The research method used is a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, documentation, and literature studies from various relevant academic sources. The results show that collaborative patterns of population data utilization are carried out through the integration of population information systems, data exchange between government agencies, and the development of information technology-based services. Public service innovations carried out include the digitization of population administration services, the use of online service information systems, and improving the quality of digital technology-based services. This collaborative data utilization can increase the effectiveness of public services and accelerate the population administration process for the community. Therefore, strengthening inter-agency coordination, improving the quality of human resources, and developing information technology infrastructure are important factors in supporting the successful utilization of population data and public service innovation.